As araucárias na terra indígena de Mangueirinha: territórios, existências e ressitência Kaingang - Branco, Carlos Frederico (2021)
This dissertation aims to understand the relationship between humans and araucarias in the Indigenous Land Mangueirinha (TIM). The research was developed through documentary and bibliographic sources. The theoretical contribution used in the research included Amerindian ethnology, ethnographies, ethno-historical and archeological works. The Kaingang, in the Indigenous TIM, have lived in forests with araucarias, fields and rivers since time immemorial and mythical. The Jê, ancestors of the Kaingang, coexist with the araucarias for at least three thousand years, producing territories and forests with them. Kaingang cosmo-ontology divides the cosmos into three levels: the numbe, the world of the dead; ga, the world of the living, and kafa, the celestial world, where Tupe, God, the Sun and the Moon meet. In ga, there are still three domains: nen, the forest; erê, the fields and the eman, the village. In all these territories the araucarias live with humans, being at the same time the border, the intermediary and the path between humans to these other worlds. With the Euro- Brazilian colonization in the Kaingang territories, both humans and araucarias began to have their territories invaded, occupied and exploited. In the 20th century, this process in the Indigenous TIM was marked by land grabbing and forest exploitation, however, the resistance caused by the ancestral alliance between humans and araucarias allowed both the forest with araucarias and the territory of the Indigenous TIM, resist the colonial advances in Mangueirinha.